Ethnobotanical and ecological perspectives on local fruits in South Kalimantan: Cultivation, trade, and conservation - Trimanto; Fauziah, Fauziah; Fiqa, Abban Putri; Wicaksono, Mohamad Hanif; Gunawan, Gunawan; Riefani, Maulana Khalid; Sujarwo, Wawan; Soendjoto, Mochamad Arief (Ethnobotany Research and Applications, 2025)
Background: Many local fruit species from Kalimantan have become rare or endangered because of land conversion and deforestation. This study aimed to document community knowledge of local fruit usage. Methods: The data were examined quantitatively via ethnobotanical measures such as the relative frequency of citation (RFC), family use value (FUV), and plant part value (PPV). We also analyzed the economic value, ecological perspective, and conservation aspects of local fruits in South Kalimantan. Results: The researchers identified 96 fruit species used by the South Kalimantan population. The highest RFC values were recorded for Artocarpus integer (0.275), Durio dulcis (0.275), Durio kutejensis (0.333), Mangifera casturi (0.373), and Mangifera similis (0.255). The families Anacardiaceae (0.123), Apocynaceae (0.176), and Malvaceae (0.157) presented the highest FUV values. Native plants were used more frequently than introduced plants. The local community has developed these fruits, preferring developed varieties over wild forest fruits. Local fruits are more abundant during the rainy than during the dry season. Most of these fruits are sold, providing economic value to the community. The local population also consumes South Kalimantan’s local fruits to fulfill their nutritional needs. Many species also face population declines and are listed on the IUCN Red List. Conclusions: Ethnobotanical studies in South Kalimantan provide insights into the importance of the relationship and utilization of local fruits by the community. Various local fruit species have economic value and potential for further development. Nevertheless, community contributions are needed to preserve the sustainability of South Kalimantan’s local fruits. Keywords: Conservation, Ethnobotany, Economic value, Local fruit, South Kalimantan